Centering Cultural Knowledge in TPACK— Evidence From a Collaborative Online International Learning Collaboration - Bae, Sohyeon; Chong, Kyle L. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
In this qualitative study, we analyzed the processes of a collaborative online international learning (COIL) collaboration between two higher education institutions in Japan and the United States from the perspective of the technological, pedagogical, and content knowledge (TPACK) framework. The research question this study aimed to address was: What is the utility of the TPACK framework, as a lens of analysis, for this online cultural exchange? To address this question, we conducted semi-structured interviews with student participants and examined their written works. From the student participants’ learning experiences, we identified evidence of cultural exchange as well as evidence of missed opportunities for cultural exchange arising from the limited knowledge of technology, pedagogy, content, and culture. COIL and TPACK both share a common goal of increasing students’ access to multiple knowledge systems using educational technology. As a result, COIL conceptually aligns well with the TPACK framework. This collaboration showed an ongoing need for the centering of cultural knowledge and cultural exchange in both COIL and TPACK. We, accordingly, outline potential for a TPACCK, a modified TPACK framework to center cultural knowledge in both with the hope of taking steps towards a more culturally sustaining framework of international collaboration.